Nouvelle approche métrique de l'épaule du genre Archaeolemur : caractéristiques morphologiques et myologiques - Beby Ramanivosoa (Revue de Primatologie)
The insularity of Madagascar allowed an important endemic fauna to develop. We can recognize subfossil lemurs, less mineralized than the fossils. They are much larger than the extant ones. They are found in sites dated to the Late Quaternary 26 000 years and 500 years BP. Within these subfossil lemurs, there is one particular genus: Archaeolemur. The morphological and myocological features studied here show that its position is closer to the extant Indriidae than to the extant Lemuridae. Its position was established using the comparison of histograms obtained for average indices of the variables measured on the scapula and the humerus. For the scapula, Archaeolemur is closer to the Indriidae for the values of 8 indices against only one for the Lemuridae. For the humerus, 7 indices are closer to the Indriidae and only 3 are close to the Lemuridae. The results show that it is necessary to consider Archaeolemur as a more arboreal animal than it was previously considered and probably climbing more.